2015
DOI: 10.1007/s10562-015-1574-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photocatalytic System Constructed Using Eosin Y, Titanium Dioxide, and Keggin-Type Platinum(II)- and Aluminum(III)-Coordinated Polyoxotungstates for Hydrogen Production from Water Under Visible Light Irradiation

Abstract: A novel photocatalytic system constructed using Eosin Y, a-Keggin-type diplatinum(II)-coordinated tungstophosphate Cs 3 [a-PW 11 O 39 {cis-Pt(NH 3 ) 2 } 2 ]Á8H 2 O (Cs-Pt-1), a-Keggin-type mono-aluminum(III)-coordinated tungstosilicate K 5 [a-SiW 11 {Al(OH 2 )}O 39 ]Á7H 2 O (KAl-1), and titanium dioxide achieved a steady rate of hydrogen evolution with highly effective utilization of platinum sites from aqueous triethanolamine solution during a long-term visible light irradiation. Graphical Abstract Eosin Y Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…TEOA was used as the sacrificial reagent. [ 13,49 ] Cs‐Si‐Pt‐300–5 , EY, and K‐Si‐Al were used as co‐catalyst, photosensitizer, and EY stabilizer, respectively. [ 13,49 ] TiO 2 was used to promote charge separation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TEOA was used as the sacrificial reagent. [ 13,49 ] Cs‐Si‐Pt‐300–5 , EY, and K‐Si‐Al were used as co‐catalyst, photosensitizer, and EY stabilizer, respectively. [ 13,49 ] TiO 2 was used to promote charge separation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13,49 ] Cs‐Si‐Pt‐300–5 , EY, and K‐Si‐Al were used as co‐catalyst, photosensitizer, and EY stabilizer, respectively. [ 13,49 ] TiO 2 was used to promote charge separation. [ 50 ] Hydrogen was formed with 100 % selectivity, and oxygen, carbon dioxide,carbon monoxide, and methane were not detected under these reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron donor in the electronic system provides electrons to photosensitizer to continue to participate in the proton reduction. 6 Moreover, some photocatalytic hydrogen production systems have successfully developed hydrogen production, while most of them have used noble metals as photocatalyst, such as platinum, 17 rhodium, 18 ruthenium, 19 and palladium. 20 Zhu et al 21 had prepared the anthryl-porphyrin functionalized platinum nanoparticle to be used as photocatalyst in the photocatalytic hydrogen production system and then explored the energy donor of anthracene substitutes and the energy acceptor of porphyrin, and it concluded that the complex nanoparticle could efficiently catalyze hydrogen generation in the photocatalytic hydrogen production system, and the total amount of hydrogen production was 175.3 μmol under UV-vis light irradiation for 12 hours.…”
Section: Introductionmentioning
confidence: 99%
“…This system achieved a steady hydrogen production during 12 h of light irradiation with highly effective utilization of the platinum sites for hydrogen production from aqueous triethanolamine (TEA) solutions under visible light irradiation (λ ≥ 400 nm, ≥440 nm, and ≥500 nm) [7]. During the light irradiation, we observed the formation of a reduced species (heteropoly blue species; HPB) of Cs-P-Pt, which was the key to achieving a steady hydrogen evolution during a 12 h of light irradiation.…”
Section: Introductionmentioning
confidence: 99%